Alston and Heyns on Unlawful Killings: A Compendium of the Jurisprudence of the United Nations Special Rapporteurs on extrajudicial, summary or arbitrary executions from 2004-2016 (Pretoria University Law Press (PULP), 2021)
This book provides a detailed overview of the law and policy related to unlawful killings and the right to life. It is organized into the key thematic issues and types of killings that arose during the mandate of the UN Special Rapporteur on extrajudicial, summary or arbitrary executions between 2004-2016. Each chapter contains an introductory overview and selected extracts from UN Special Rapporteur reports to the United Nations General Assembly and the Human Rights Council and other normative work, and covers the applicable international law, policy considerations, and common fact scenarios.